OC-053 LONG-TERM FOLLOW-UP OF A SLOWLY RESORBABLE BIOSYNTHETIC MESH IN VHWG GRADE 3 HERNIA REPAIR. (13th October 2022) - Van Den Dop, M; Tollens, T; Jørgensen, L; De Vries-Reilingh, T; Piessen, G; Köckerling, F; Miserez, M; Dean, M; Berrevoet, F; Dousset, B; Van Westreenen, G; Gosetti, F; et al.
Abstract: Background: Incisional hernia recurrence occurs frequently after initial repair. In potentially contaminated hernia, these numbers can rise up to 50%. Recently, resorbable meshes have been used to prevent infection in complicated incisional hernia and prevent long term mesh complications. Present study focuses on the long term outcomes of a resorbable mesh. Methods: Patients included in the priorly conducted Phasix trial with Ventral Hernia Working Group (VHWG) grade 3 hernia were invited for an abdominal CT scan and physical examination. Primary outcome was hernia recurrence, secondary outcomes comprised of abdominal wall configuration, mesh resorption and long term mesh complications. Results: Of the 84 patients included in the 2-year follow-up, 56 were available for long term follow-up up to five years. Mean follow-up time was 4.2 years. CT scan was made in 36 (64.3%) of patients. Kaplan-Meier analysis showed a recurrence rate of 16.7% after five years. Four (7.1%) new recurrences were found between 2-year and 4.2 years follow-up of which three by CT scan. In 50% of CT scans, no signs of postoperative distortions of the abdominal wall were observed. No long term mesh complications were reported. Conclusion: After long term follow-up, VHWG 3 hernia repair with biosynthetic mesh demonstrated good performance with regard to hernia recurrence. Possibly, tissue reconstruction took place in the first two years after implantation by the use it or lose it principle, which led to sufficient native abdominal wall strength to prevent recurrences after resorption of the mesh.